Analisa Yuridis Perlindungan Hukum Terhadap Penerima Pinjaman Online Berdasarkan Perlindungan Data Pribadi Kadek Julia Mahadewi - Julia Mahadewi, Kadek (Media Bina Ilmiah, 2023)
The existence of Covid 19 was able to create economic instability, both national and international, one of the impacts that occurred was the difficulty of earning felt by the community so that using the use of technological advances by making online loans was felt to be easier than making loans at banks which were felt to be more severe. The high number of online loans every year is also causing many problems to occur in society, the interest offered is higher, and if there is a delay in payment, online loans will spread personal data to the contact recipients of the loan. The provisions of the Financial Services Authority Regulation Number 10 of 2022 article 44 are vague, so it needs to be analyzed more deeply regarding the urgency of the the existence of the Personal Data Protection Law Article 36 in regulating the existence of loans that are felt to be felt by the community. The problems obtained by How are legal consequences of online loans? How is legal protection for online loan recipients? The purpose of writing this journal is to provide public insight into the legal influence of personal data protection in online loans. The writing method uses normative legal research, a statutory approach and primary and secondary legal sources. The results of the discussion of online loans using electronic agreements where these agreements are categorized as bad 90day. Reports of the spread of personal data and terror obtained by loan recipients led to an analysis of Article 36 of the PDP Law Keywords: legal protection; online loans; personal data